Abdominal migraine in childhood: a review - Scicchitano B; Humphreys G; Mitton SG; Jaiganesh T (Dove Medical Press, 2014)
Beatrice Scicchitano,1 Gareth Humphreys,1 Sally G Mitton,2 Thiagarajan Jaiganesh1 1Children's Emergency Department, 2Department of Paediatric Gastroenterology, St Georges Hospital, St Georges Healthcare NHS Trust, Tooting, London, United Kingdom Abstract: The childhood condition of abdominal migraine has been described under many different synonyms, including "abdominal epilepsy", "recurrent abdominal pain", "cyclical vomiting syndrome", and "functional gastrointestinal disorder". In the early literature, abdominal migraine is included in the "childhood periodic syndrome", first described by Wyllie and Schlesinger in 1933. Abdominal migraine has emerged over the last century as a diagnostic entity in its own right thanks to the development of well defined diagnostic criteria and its recent inclusion in the International Headache Society's Classification of Headache disorders. Despite this progress, little is known about the pathophysiology of the condition, and the treatment options are poorly defined. Here we summarize the recent literature, with particular focus on establishing the diagnosis of abdominal migraine and its pathophysiology, and suggest an approach to management. Keywords: abdominal migraine, recurrent abdominal pain, abdominal epilepsy, cyclical vomiting